Cesium carbonate mediated C–H functionalization of perhalogenated 12-vertex carborane anions. Issue 25 (9th March 2022) - Lovera, Sergio O.; Bagsdasarian, Alex L.; Guo, Juchen; Nelson, Hosea M.; Lavallo, Vincent
Abstract : C–H functionalization of undecahalogenated carborane anions, [HCB11 X11 − ] (X = Cl, Br, I), is performed with Cs2 CO3 in acetonitrile. Abstract : C–H functionalization of undecahalogenated carborane anions, [HCB11 X11 − ] (X = Cl, Br, I), is performed with Cs2 CO3 in acetonitrile. We show that the requisite Cl, Br and I carborane dianions can all be efficiently accessed with Cs2 CO3 . The utilization of Cs2 CO3 eliminates the complications associated with competing E2 elimination reactions providing an efficient, more functional group tolerant, and broader scope than previously reported. The ensuing functionalized cages provide potential synthons for constructing advanced materials and other molecular architectures for various applications.